Cationic Polymerization of 1,3-dioxolane Using Sacrificial Anodes - Djelali, N-E.; Aliouche, D.; Daddi Oubeka, L.; Pierre, G. (Asian Journal of Chemistry, 2010)
The electroinitiated polymerization of 1,3-dioxolane is carried out with metallic cationic initiators generated electrochemically V, Hg, Cr, Al.